Autobiography : I wonder as I wander - Hughes, Langston, 1902-1967 (Hughes, Langston, 1902-1967. Works., 2003)
I Wonder As I Wander (1956), Hughes's second volume of autobiography, is a continuation from The Big Sea, detailing his global travels to such areas as Cuba, Haiti, Paris, the Soviet Union, and the Far East. It culminates in his 1937 coverage for the Baltimore Afro-American of the Spanish Civil War. The travelogue highlights the beginning of Hughes's career as a journalist, a further realization of his goal to live as a professional writer. Furthermore, it shows the influence of legendary black educator Mary McLeod Bethune, who inspired Hughes to travel through the South giving readings of his poetry. His recollections of American journeys place him as well in Carmel, California, and the San Francisco area, where he was befriended by Noël Sullivan and was among the set of Hollywood personalities sometimes including James Cagney, Greta Garbo, Jean Harlow, as well as Indian mystic J. Krishnamurti. Hughes also shows readers the lighter side of his adventures in the Caribbean, where he experienced the rhythms of Afro-Cuban music and the wonders of such sights as the Citadel in Haiti. In 1932, having traveled with a group of African Americans to the Soviet Union to make a film about southern black steelworkers and domestic laborers, Hughes became familiar not only with Moscow's theatrical life but also with "colored" minorities in the new republics of Soviet Central Asia. As a wanderer, he carried with him a record player and a collection of jazz recordings and became an informal participant in "cultural exchange." For Hughes, the lack of appreciation of jazz by Russian ideologues was a major flaw in the system. In Tokyo and Shanghai, he learned about Asian global politics and tough street life, and in Paris he reacquainted himself with its nightlife and such personalities as Ada "Bricktop" Smith and Josephine Baker. Throughout his journey, he observed the presence of blacks, whether as entertainers in major capitals or as soldiers on the battlefront in Barcelona and Madrid. His coverage of the Spanish Civil War is a serious report of the tragedy of conscripted North African Moors and the heroic efforts of the International Brigades and such African Americans as Milton Herndon in their fight against fascism. Spain is also a window into flamenco musical culture, where singers such as Pastora Pavón offer their own form of the blues. In rare moments, Hughes reveals aspects of his personal romantic encounters. Also of great interest are his recollections of writers Arthur Koestler, Nicolás Guillén, Pablo Neruda, and Ernest Hemingway. I Wonder As I Wander shows how Hughes maintained a Harlem-derived black consciousness, while expanding it through global wandering.